2020
DOI: 10.1007/978-981-15-5894-8
|View full text |Cite
|
Sign up to set email alerts
|

CEFR-informed Learning, Teaching and Assessment

Abstract: Texts in Education delivers high-quality instructional content for graduates and advanced graduates in all areas of Education and Educational Research. The textbook series is comprised of self-contained books with a broad and comprehensive coverage that are suitable for class as well as for individual self-study. All texts are authored by established experts in their fields and offer a solid methodological background, accompanied by pedagogical materials to serve students such as practical examples, exercises,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…As mentioned, it was anticipated that the teams would be grouped thematically around the five central themes: (1) designing a curriculum and / or course, (2) materials development, (3) classroom implementation, (4) assessment, and (5) learner autonomy and the European Language Portfolio. These categories roughly follow the chapters of Nagai et al (2020). Yet, feedback from the introductory forum, workshop and a review of the participants' workbooks revealed a more complex and diverse scenario than expected.…”
Section: Reflection and Challenges From The First Year Of The Kaken P...mentioning
confidence: 93%
See 3 more Smart Citations
“…As mentioned, it was anticipated that the teams would be grouped thematically around the five central themes: (1) designing a curriculum and / or course, (2) materials development, (3) classroom implementation, (4) assessment, and (5) learner autonomy and the European Language Portfolio. These categories roughly follow the chapters of Nagai et al (2020). Yet, feedback from the introductory forum, workshop and a review of the participants' workbooks revealed a more complex and diverse scenario than expected.…”
Section: Reflection and Challenges From The First Year Of The Kaken P...mentioning
confidence: 93%
“…It starts by describing why action research is the perfect vehicle for teachers to systematically research putting CEFR educational principles into practice. The following section, a brief overview of the CEFR, is based on the CEFR & LP SIG's latest publication, CEFR-informed Learning, Teaching and Assessment: A Practical Guide (Nagai et al 2020). An overview of action research is then provided, and includes an introduction to various AR models, ranging from the traditional (Kemmis and McTaggart 1988) to the more recent (Mertler 2020;Mills 2018).…”
Section: Foreign Language Education Reform Through Action Research-pu...mentioning
confidence: 99%
See 2 more Smart Citations
“…Students will have a deep understanding of a concept for doing and observe directly. Direct experience that will make learning meaningful [3].…”
Section: Introductionmentioning
confidence: 99%